1996
DOI: 10.1128/aem.62.12.4556-4562.1996
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dechlorination of historically present and freshly spiked chlorinated dioxins and diversity of dioxin-dechlorinating populations

Abstract: The ability of a microbial consortium eluted from dioxin-contaminated Passaic River sediments to dechlorinate polychlorinated dibenzo-p-dioxins (PCDDs) was investigated under methanogenic conditions. Aged 2,3,7,8-tetraCDD, which had partitioned into the microbial consortium from sediments, was stoichiometrically converted to tri-and monoCDD congeners. During dechlorination, dominant microbial activity within the consortium shifted from methanogenic to nonmethanogenic activity. Freshly spiked octaCDD was conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 33 publications
5
90
1
Order By: Relevance
“…A potential drawback of dechlorination is that the potential removal of chlorines from the 1-, 4-, 6-, and 9 positions from octachlorodibenzo-p-dioxin form 2,3,7,8-tetrachlorodibenzo-p-dioxin (TeCDD) and other 2,3,7,8-substituted congeners that are considered to be potential human carcinogens [3]. Dechlorination of CDD/Fs in sediments may be the result of a combination of both respiratory and cometabolic microbial processes [6,7,[9][10][11][12][13] in addition to a variety of abiotic mechanisms [7,[14][15][16]. In most cases, CDD/F contamination occurs at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A potential drawback of dechlorination is that the potential removal of chlorines from the 1-, 4-, 6-, and 9 positions from octachlorodibenzo-p-dioxin form 2,3,7,8-tetrachlorodibenzo-p-dioxin (TeCDD) and other 2,3,7,8-substituted congeners that are considered to be potential human carcinogens [3]. Dechlorination of CDD/Fs in sediments may be the result of a combination of both respiratory and cometabolic microbial processes [6,7,[9][10][11][12][13] in addition to a variety of abiotic mechanisms [7,[14][15][16]. In most cases, CDD/F contamination occurs at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This activity was first indicated by changes in the dioxin congener patterns as well as build-up of lightly chlorinated analogues in anaerobic environments (Townsend 1983). Anaerobic microbial community was implicated in the reductive dehalogenation of highly chlorinated PCDD/Fs in contaminated sediments, sludges, and soils (Barkovskii and Adriaens 1996;Yoshida et al 2005). However, microbial dechlorination of highly chlorinated analogues produces most toxic congeners, i.e., 2,3,7,8-TCDD as an intermediate due to deletion of chlorine at positions 1, 4, 6 and/ or 9 (Barkovskii and Adriaens 1996).…”
Section: Bacterial Transformation and Degradation Of Dioxinsmentioning
confidence: 99%
“…For example, the availability of DDT and DDE to the earthworm Eisenia fetida was reduced by up to 90 percent, although the chemical concentration in the soil remained relatively constant (Morrison et al, 2000). Similarly, reduced availability was also observed for other halogenated aromatic pesticides, PCDD/Fs, and PAHs (Alexander, 2000;Guthrie-Nichols et al, 2003).Toxicological studies have shown that less 2,3,7,8-TCDD was absorbed by mammals after it had been in soil for only eight days (Barkovskii & Adriaens, 1996). It was suggested that the assimilation and acute and chronic toxicity of these compounds decline with residence time as they become increasingly sequestered (Alexander, 2000).…”
Section: Field and Laboratory Evidencementioning
confidence: 99%